Rekonstruksi Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah - Alexander Zulkarnaen Fauzi; Yulinartati Yulinartati; Elok Fitriya (BUDGETING : Journal of Business, Management and Accounting, 2021)
This study aimed to determine the financial statements of Bestcow dairy farm based on the Financial Accounting Standards of Micro, Small, and Medium Enterprises. Interview, observation, and documentation as a method of data collection and data sources obtained from primary and secondary data. The research method used in this study is a qualitative method. This research is a case study with the object of research on Bestcow dairy farm which has not implemented the preparation of financial statements with SAK EMKM. The results showed, income statement with total loss Rp. 33.083.780, financial position statement with total asset of Rp 1.452.653.220, Note to the financial statement (CALK) presented a general description of UMKM Bestcow. Conclusion, that Bestcow dairy farm in preparing its financial statements only prepared a simple financial statement Keywords : Preparation of Financial Statement, SAK EMKM